2015
DOI: 10.1007/s10843-015-0161-9
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of risk and entrepreneurial attitudes of university students in the USA and Brazil

Abstract: There is a long-standing debate about whether entrepreneurs and nonentrepreneurs differ in risk aversion levels. The paper addresses international differences in risk and entrepreneurial attitudes of university students, specifically in the USA and Brazil. This paper also aims to add to the ongoing debate surrounding the risk attitudes of entrepreneurial persons when compared to non-entrepreneurial persons. The data from the paper was generated from an economic experiment. The economic experiment included a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In addition, as in previous studies, students' age has also been included as an additional control (Barber 2015;Minola et al 2016;Criaco et al 2017;Laskovaia et al 2017;Morris et al 2017;Smolka et al 2018). Students' age can be correlated with entrepreneurial risk taking (Barber 2015). Previous works have shown that age is correlated with entrepreneurial intention (Hatten and Ruhland 1995;Harada 2003;Schwarz et al 2009;Criaco et al 2017;Smolka et al 2018).…”
Section: Variablesmentioning
confidence: 95%
See 3 more Smart Citations
“…In addition, as in previous studies, students' age has also been included as an additional control (Barber 2015;Minola et al 2016;Criaco et al 2017;Laskovaia et al 2017;Morris et al 2017;Smolka et al 2018). Students' age can be correlated with entrepreneurial risk taking (Barber 2015). Previous works have shown that age is correlated with entrepreneurial intention (Hatten and Ruhland 1995;Harada 2003;Schwarz et al 2009;Criaco et al 2017;Smolka et al 2018).…”
Section: Variablesmentioning
confidence: 95%
“…Empirical evidence also indicates that, despite the growth in female entrepreneurship, men entrepreneurs are still almost twice as many as women entrepreneurs (Bosma and Levie 2009). In addition, as in previous studies, students' age has also been included as an additional control (Barber 2015;Minola et al 2016;Criaco et al 2017;Laskovaia et al 2017;Morris et al 2017;Smolka et al 2018). Students' age can be correlated with entrepreneurial risk taking (Barber 2015).…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has been conducted to examine the relationship between risk and entrepreneurial intention or decision. The majority merely compares the risk preferences of entrepreneurs with those of employed individuals to find potential differences [4,13,14]. The role of an individual's risk preferences at the time that person decides to become selfemployed remains largely untested [15].…”
Section: Introductionmentioning
confidence: 99%